212k views
1 vote
Please help me solve this

Please help me solve this-example-1
User Plaxdan
by
4.9k points

2 Answers

5 votes

Answer:

(1,-2)

Explanation:

To solve this using substitution, lets look at the main equation:

5x + y = 3

We know that y = -2x

So lets substitute that in:

5x + (-2x) = 3

Simplify to get:

3x = 3,

-> x = 1

Now to figure out y, lets plug it into the original equation:

y = -2x

-> y = -2(1)

y = -2

So the ordered pair is (1,-2)

User Adrien Joly
by
4.9k points
0 votes

Answer:

(1,-2)

Explanation:

Right Answer

User Burhan Khanzada
by
4.8k points